Combined microneurosurgical and endovascular "Trapping-Evacuation" technique for clipping proximal paraclinoidal aneurysms - Albert, Friedrich; Forsting, Michael; Kummer, Rüdiger von; Aschoff, Alfred; Kunze, Stefan (Skull base, 1995)
Thieme E-Books & E-Journals
Elektronische Reproduktion der Druck-Ausgabe 3. März 2008
Gesehen am 12.09.2023